Hydrogen storage in Zr0.9Ti0.1(Ni0.5Cr0.5-xVx)2 Laves phase, with x = 0, 0.125, 0.25, 0.375, 0.5. A theoretical approach. (16th August 2018) - Robina, A.; Bechthold, P.; Juan, A.; Pistonesi, C.; Pronsato, M.E.
Abstract: Density functional calculations were performed on Zr0.9 Ti0.1 (Ni0.5 Cr0.5-x Vx )2 Laves Phase, with x = 0, 0.125, 0.25, 0.375 and 0.5, in order to study its H absorption capacity. Binding energy, electronic structure and bonding were analyzed for the intermetallic compound with different V content and increasing amounts of hydrogen. The optimized geometry was found in good agreement with experimental data of the C14 Laves phase. Hydrogen locates preferentially in A2 B2 tetrahedral sites in the AB2 matrix (A = Zr, Ti; B = Ni, Cr, V) but AB3 and B4 sites are also stable. The volume of the intermetallic and the H binding energy increases with vanadium content. Theoretically H absorption is possible up to 4.5 H/F.U. but the strongest binding energy is achieved with 3 H/F. U. The main contribution to density of states is due to d states of all components of the structure and an H-metal bonding is observed in the range −10 to −4 eV. Highlights: Substituting Cr by V in Zr0.9 Ti0.1 (Ni0.5 Cr0.5-x Vx )2 increases the cell volume. H binds stronger with increasing V content in the system. There is a strong charge transfer from Ni, Cr and V atoms towards H. The charge transfer increases with the V content in the system. The presence of hydrogen produces a new band at lower energy values.